1994
DOI: 10.1016/0370-2693(94)90265-8
|View full text |Cite
|
Sign up to set email alerts
|

Strange particle freeze-out

Abstract: We reconsider thermal conditions of the central fireball presumed to be the source of abundantly produced strange (anti-)baryons in S → W collisions at 200 GeV A. We show that it is possible to completely fix the freeze-out temperature of strange particles in terms of the central rapidity kaon to Lambda particle abundance ratio at fixed, high transverse mass using a non-equilibrium hadronization model and the measured quark fugacities.Kinetic strange particle production models [1] imply that abundant strangene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…These ratios can be calculated assuming either a hadron gas scenario or a quark-gluon plasma scenario, and a comparison can be made of the values extracted from the models in the two scenarios in conjunction with other thermodynamic variables of the system, such as the temperature T , the baryo-chemical potential µ B , and the entropy [141,142].…”
Section: Strangeness Enhancementmentioning
confidence: 99%
“…These ratios can be calculated assuming either a hadron gas scenario or a quark-gluon plasma scenario, and a comparison can be made of the values extracted from the models in the two scenarios in conjunction with other thermodynamic variables of the system, such as the temperature T , the baryo-chemical potential µ B , and the entropy [141,142].…”
Section: Strangeness Enhancementmentioning
confidence: 99%
“…Different analyses of data at AGS and CERN/SPS energies have shown that the experimental results may be described as a transversally and longitudinally expanding chemically and thermally equilibrated hadrongas [217,220,221,284]. The assumption of a chemically and thermally equilibrated source, however, implies a uniform freeze-out for all particles; i.e.…”
Section: Particle Freeze-outmentioning
confidence: 99%
“…In addition they have been applied to study the degree of chemical equilibration in a relativistic heavy-ion reaction. Bulk properties like temperatures, entropies and chemical potentials of highly excited hadronic matter have been extracted assuming thermal and chemical equilibrium [14,7,144,211,212,213,6,214,215,216,217,218,219,220,221]. Recent SPS data on hadron yields and ratios have been fit either in the framework of a hadronizing QGP droplet [211,222,223,224] or of a hadron gas in thermal and chemical equilibrium [221] (including elementary proton-proton interactions [144]).…”
Section: Hadrochemistry: Multiplicities and Ratiosmentioning
confidence: 99%
“…Hadron yields and their ratios stemming from the final state of ultra-relativistic heavyion collisions have been extensively used to explore the degree of chemical equilibration [ 1,2,3,4,5,6,7,8,9,10] and to search for evidence for exotic states and phase transitions in such collisions [ 1]. Under the assumption of thermal and chemical equilibrium, fits with a statistical (thermal) model have been used to extract bulk properties of hot and dense matter, e.g.…”
Section: Introductionmentioning
confidence: 99%